Implementation of the Digitalization Acceleration Policy at the Ministry of Communication and Informatics - Saedini, Selva; Soemartono, Triyuni; Nenobais, Harry (Jurnal Jembatan Efektivitas Ilmu dan Akhlak Ahlussunah Wal Jama'ah, 2025)
Study purpose.. The objective of this study is to analyse the implementation of the national television digitalisation acceleration policy at the Ministry of Communication and Information Technology. Materials and Methods. The method used is a descriptive qualitative method with data collection techniques in the form of observation, literature study, in-depth interviews, and documentation. This study utilised Edward Gerston's policy implementation theory, which includes translation ability, resources, limited number of players, and accountability. To enrich the analysis, Van Metter and Van Horn's policy implementation theory was also used, which covers the size and objectives of the policy, resources, characteristics of implementing agents, tendencies of implementers, inter-organisational communication, and the social, economic, and political environment. Results. The results of the study indicate that in the digitalisation process, the need for trained workers is very important in order to cope with technological changes. Television digitalisation was developed for the public interest, where television as a medium of information helps shape public behaviour through the content it broadcasts. Educational programmes are a strategic instrument in educating the nation. The implementation of Analog Switch-Off (ASO) provides the public with access to more efficient and optimal broadcasting quality. Digitalisation also drives innovation, job creation, increased productivity, and provides beneficial economic impacts through digital dividends. Conclusion. However, the implementation of this policy faces challenges, including infrastructure readiness, the provision of equipment such as set-top boxes, and disparities in public adaptation to digital technology. In this context, the Ministry of Communication and Information Technology plays a central role in regulating and accelerating digitalisation through strategic and adaptive policies. This study provides an in-depth description of the urgency and dynamics of implementing digital broadcasting policies in Indonesia.